(untitled) (Journal of the College of Basic Education, 2022)
The current research is interested in studying the formal, functional, aesthetic and technical characteristics and their displacements in the arts of postmodern ceramics (American ceramics), which were embodied by a number of potters, for a specific period of time, and with multiple subjects with different materials. To form a kind of assimilation of the shape of the American ceramic artist in all of his works, which in turn takes (displacement) as transforming factors in form, function, beauty, and color technique. And what it includes of artistic, aesthetic and expressive characteristics by which the artist achieves the development of his meanings in an artistic language that crossed modernity and formulated the manifestations of texts that break the pattern of ceramic work.